Estudo etnobotânico de espécies alimentícias na Zona de Amortecimento do Parque Nacional das Sete Cidades, Piauí, Brasil - Santos, Emanuela Gonçalves dos (2023)
An important characteristic of family agriculture is its diversity of food species, composing agrobiodiversity and helping with food and nutritional security, which is strongly influenced by agroforestry homegardens. In this context, agriculture is present practically throughout the country, comprising various edaphoclimatic characteristics and cultures, even in Buffer Zones. Based on these aspects, this study aimed to record the diversity of food species in the Buffer Zone of the “Sete Cidades” National Park, in the rural community of Cachoeira (Piauí, Brazil), seeking to understand the dynamics of which parts are used and the forms of preparation and consumption, in addition to investigating whether there is a consensus among the interviewees about the species they mentioned and a difference in the citations between men and women, using the Local Value (LV) as a parameter. All the residences in the community were visited and all the householders were interviewed, focusing on those whose areas were considered as agroforestry homegardens. The data were obtained through semi-structured interviews and complemented by informal conversations. The vernacular names of the cited species were recorded according to the informants. The data were organized in spreadsheets and analyzed both from the perspective of a general context and agroforestry homegardens, recording the botanical families and food species mentioned by the residents, considering their origin, and classifying them as native or exotic, as well as their habits. The plant parts used by the community and the forms of consumption and preparation were also analyzed. The Informant Consensus Factor (ICF) and the LV were calculated, seeking to find differences in knowledge between men and women. The Spearman test was used to verify correlations between the size of the homegardens and the number of species mentioned. The results obtained by calculating the LV were tested using the Mann-Whitney test to verify significant differences between genders. Thirteen men (48.14%) and 14 women (51.86%) were interviewed in the general context and 9 men (52.94%) and 8 women (47.06%) regarding the homegardens. A total of 295 citations of food uses were recorded, distributed in 58 species, belonging to 26 botanical families, which included 26 native (53.06%) and 23 exotic (46.94%) species. For the homegardens, 130 citations of uses were recorded, distributed in 33 species, belonging to 20 botanical families, including 10 native (30.30%) and 23 exotic (69.70%) species. Anacardiaceae was the most prominent family, considering the number of species. Tree habit stood out among the forms of life and the fruit was the plant part most cited in the community, as well as the consumption in natura. Regarding LV, Caryocar cuneatum Wittm. (pequi) was the most important species for men and women. The ICF was 0.81 for the general context and 0.75 for the agroforestry homegardens, indicating a considerable degree of consensus among the residents. The Spearman’s correlation coefficient was 0.576, indicating moderate correlation. The statistical analysis showed no significant differences in knowledge between genders.